How Focusing on Superordinate Goals Motivates Broad, Long-Term Goal Pursuit: A Theoretical Perspective - Höchli, Bettina; Brügger, Adrian; Messner, Claude (Frontiers in Psychology, 2018)
Goal-setting theory states that challenging, specific, and concrete goals (i.e., subordinate goals) are powerful motivators and boost performance in goal pursuit more than vague or abstract goals (i.e., superordinate goals). Goal-setting theory predominantly focuses on single, short-term goals and less on broad, long-term challenges. This review article extends goal-setting theory and argues that superordinate goals also fulfill a crucial role in motivating behavior, particularly when addressing broad, long-term challenges. The purpose of this article is to show theoretically that people pursue long-term goals more successfully when they focus on subordinate and superordinate goals simultaneously than when they focus on either subordinate or superordinate goals alone.